2020
DOI: 10.2174/1389202921666200327105756
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of a Highly Virulent pvl-positive Vancomycin intermediate- resistant Staphylococcus aureus Sequence Type 30

Abstract: Background: Staphylococcus aureus isolates expressing the Panton-Valentine Leukocidin (PVL) have been related to a wide range of diseases. Recently, pvl-positive community-associated methicillin-resistant S. aureus belonging to USA1100 (ST30/CC30/SCCmec IV) lineage has emerged in Brazilian hospitals. Objective: The aim of this work was to sequence the genome of a pvl-positive USA1100 Vancomycin- Intermediate-Resistant S. aureus (VISA) isolate from Rio de Janeiro, Brazil. Methods: The 13420 genome was seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The hVISA phenotype is commonly reported in MRSA strains belonging to ST5, ST8 and ST239. However, the hVISA strain recovered in this research, corresponding to ST30, exhibited similar microbiological characteristics to an hVISA strain isolated from a neonate's blood culture in Brazil in 2009 [10]. The ST30 (CC30) has been circulating in the region and Uruguay since the beginning of the burden of community-acquired MRSA (CA-MRSA) infections and remains present today [12][13][14].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The hVISA phenotype is commonly reported in MRSA strains belonging to ST5, ST8 and ST239. However, the hVISA strain recovered in this research, corresponding to ST30, exhibited similar microbiological characteristics to an hVISA strain isolated from a neonate's blood culture in Brazil in 2009 [10]. The ST30 (CC30) has been circulating in the region and Uruguay since the beginning of the burden of community-acquired MRSA (CA-MRSA) infections and remains present today [12][13][14].…”
Section: Discussionmentioning
confidence: 63%
“…However, the hVISA strain #7 was SCCmec IV and did not show a multidrugresistant phenotype. On the other hand, in the neighboring countries Argentina and Brazil, there are descriptions of hVISA strains in both multidrug-resistant and non-multidrugresistant MRSA phenotypes [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by our group [16], we showed that a H2b PVL-positive USA1100/ST30/CC30 isolate expressed five times more PVL mRNA when compared with other lineages of S. aureus. It is important to point that this isolate was recovered from a neonate bloodstream infection.…”
mentioning
confidence: 79%